INFLUENCE OF FIRM SIZE, INDUSTRY GROUP, ROE WITH CORPORATE DISCLOSURE AND ITS IMPACT TOWARDS ENVIRONMENTAL DISCLOSURE FOR COMPANIES LISTED AT THE JAKARTA STOCK EXCHANGE - Bambang Sudaryono (Media Riset Akuntansi, Auditing & Informasi, 2007)
This study investigates the interaction and influence of firm size, industry group, ROE with corporate disclosure and its impact towards environmental disclosure for companies listed at the Jakarta Stock Exchange, on 691isted companies. The type of this research was explana-tory research. The method of analysis of this researrh used linear regression method to examine association between dependent and independent variables. The results show that the independent variables simultaneously influence firm size, industry group, ROE with corporate disclosure on corporate disclosure were tested with level of effect are weak in the range of 9,5% and simultaneously the effect of fiM1 size, industry group, ROE with corporate disclosure and its impact towards environmental disclosure are moderate in the amount of 63%. The difference of the result was caused bydifferent industry groups characteristics and firm size company listed in capital market in Indonesia.Keywords: firm size, industry group, ROE, corporate disclosure and environmental disclosu